HUBUNGAN OBESITAS DAN KEBIASAAN MINUM KOPI DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS MASBAGIK BARU KABUPATEN LOMBOK TIMUR - Aprilia Rahmawati; Mamang Bagiansah; Alfian Muhajir; Buly Fatrahady Utama (Nusantara Hasana Journal, 2023)
An abnormal increase in blood pressure can be a major cause of cardiovascular disease. Hypertension is divided into three groups, namely mixed hypertension, systolic hypertension and diastolic hypertension. Some of the risk factors that cause hypertension are age, gender, heredity, smoking habits, stress, lack of exercise, alcohol, salt, obesity and coffee drinking habits. To determine the relationship between obesity and coffee drinking habits with the incidence of hypertension in the working area of the Masbagik Baru Health Center, East Lombok Regency. Observational analytic quantitative research with a cross sectional study design. The sampling technique used purposive sampling. The research was conducted in the working area of the Masbagik Baru Health Center, East Lombok Regency, on January 13, 2023. The research sample was 100 respondents. The data obtained were analyzed by Chi Square correlation test.There is a relationship between obesity and the incidence of hypertension in the working area of the Masbagik Baru Health Center, East Lombok Regency with a P-Value of 0.002. There is a relationship between the habit of drinking coffee and the incidence of hypertension in the working area of the Masbagik Baru Health Center, East Lombok Regency with a P-value of 0.030.